PENGARUH PENGETAHUAN DAN SIKAP BIDAN TERHADAP TINDAKAN BIDAN DALAM INISIASI MENYUSUI DINI (IMD) PADA IBU BERSALIN - Wasiah, Wasiah (Jurnal Kesehatan Samodra Ilmu (JKSI), 2023)
Based on the results of the Indonesian Demographic and Health Survey (SDKI) in 2017, the Infant Mortality Rate (IMR) shows 24 per 1000 live births, the Neonatal Mortality Rate (AKN) is 15 per 1000 live births and the Infant Mortality Rate (AKABA) is 32 per 1000 live births. However, the mortality rate for neonates, infants and toddlers is expected to continue to decline. Interventions that can support child survival are shown to be able to reduce IMR to 10 per 1000 live births and IMR to 16 per 1000 live births in 2024. Meanwhile, in accordance with sustainable development targets. AKABA is expected to reach 18.8 per 1000 live births in 2030. In recent years, the government has begun to aggressively promote the provision of IMD from the first hour of birth for babies aged 0-6 months. This effort received very good support and broad coverage, one of which was from the Association of Indonesian Breastfeeding Mothers (AIMI), the aim of the research was to determine the influence of Midwives' Knowledge and Attitudes on Midwives' Actions in Early Breastfeeding Initiation in Maternity Women. This research method uses a systematic literature review of 6 articles, carried out via the Google Scholar search engine using Indonesian, in selecting research articles using inclusion criteria, namely the theme of the article content, time period, year of publication, language, subject, method, sample and type of article. , for exclusion criteria including the theme of the article content, time period, type of article. The results of the research showed that 4 articles stated that there was an influence of knowledge and attitudes on IMD measures for mothers in labor, while 2 studies stated that there was no influence of knowledge and attitudes towards IMD measures for mothers in labor. Conclusions from the research include the influence of midwives' knowledge and attitudes on midwives' actions in IMD for women giving birth. Suggestions for midwives can increase their knowledge and attitudes by attending higher education, training, workshop, seminars and seeking information about IMD.